Brain Apparent Diffusion Coefficient Decrease During Correction of Severe Hypernatremic Dehydration - Righini, Andrea (AJNR Am J Neuroradiol, 2005)
Summary: We report on the brain diffusion MR imaging findings in a neonate with severe hypernatremic dehydration, which resulted in cerebral edema (osmotic edema) and in apparent diffusion coefficient decrease, despite a careful and slow rehydration. This report provides in vivo insight into nervous cell response to osmotic challenge.